ABOUT DEVELOPMENT OF MEASURES OF TRUST AND TRANSPARENCY IN A CONTEXT OF CALLS AND THREATS - A. Y. Malov (Vestnik MGIMO-Universiteta, 2013)
The article is devoted to the analysis of the role and significance of the transparency and confidencebuilding measures (TCBMs) in respect to outer space activities. The article examines the TCBMs role in international legal instruments and peculiarities of their elaboration and implementation in the sphere of space activities security. Historical aspects as well as the significance of the issue promotion for creating the conditions allowing to ensure the prevention of placement of weapons in outer space are anylized. The article contains the prognosis of a possible outcome of the UN Group of governmental experts work on TCBMs in outer space activities. The Russian experts continue now work on generalization and classification of concrete MTDK in the form of the draft of the catalog of measures for ensuring transparency and trust in space activity. In case of its realization it could become a component of the researches presented to the report of the Secretary general to General Assembly at its sixty eighth session in pursuance of the resolution 65/68 8 of December, 2010. Such catalog would be the systematized arch of TCBMs intended for use in the international practice on a voluntary basis. It could contain the main data on TCBMs: to their structure on a target orientation; categories MTDK; the information passport of each measure – the name, mission, the contents, scope of application, a format, a procedure, the questions which decision is necessary for its realization; possible forms of use of TCBMs on a unilateral, bilateral and multilateral basis by means of the corresponding mechanisms and the procedures being a subject of coordination between the states, expressed desire to use TCBMs in relation to the space activity.